2019
DOI: 10.3390/nano9070992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2-ZnO-MgO Mixed Oxide on Microbial Growth and Toxicity against Artemia salina

Abstract: Mixed oxide nanoparticles (MONs, TiO2–ZnO–MgO) obtained by the sol-gel method were characterized by transmission electron microscopy, (TEM, HRTEM, and SAED) and thermogravimetric analysis (TGA/DTGA–DTA). Furthermore, the effect of MONs on microbial growth (growth profiling curve, lethal and sublethal effect) of Escherichia coli, Salmonella paratyphi, Staphylococcus aureus and Listeria monocytogenes, as well as the toxicity against Artemia salina by the lethal concentration test (LC50) were evaluated. MONs exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 70 publications
1
19
1
Order By: Relevance
“…Li-doped MgO NPs are more efficient than pure MgO, whereas Zn and Ti-doped MgO exhibit lower antibacterial activity than MgO [ 22 ]. TiO 2 -ZnO-MgO mixed oxides nanomaterials have a strong antibacterial effect against Gram-negative and Gram-positive bacteria [ 141 ].…”
Section: Metal Oxide Nanocomposites Against Plankton Cells and Biomentioning
confidence: 99%
“…Li-doped MgO NPs are more efficient than pure MgO, whereas Zn and Ti-doped MgO exhibit lower antibacterial activity than MgO [ 22 ]. TiO 2 -ZnO-MgO mixed oxides nanomaterials have a strong antibacterial effect against Gram-negative and Gram-positive bacteria [ 141 ].…”
Section: Metal Oxide Nanocomposites Against Plankton Cells and Biomentioning
confidence: 99%
“…At the concentration of 500 μg TiO 2 /mL, NPs inhibited the growth of the probiotic formulation by 66 ± 6.1% and 71 ± 5.6% in anaerobic and aerobic conditions, respectively. Significant reduction in the count of E. coli (ATCC 8739), Salmonella paratyphi (ATCC 9150), and L. monocytogenes (ATCC 15,313) (reduction log CFU 0.95 ± 0.01, 0.66 ± 0.01, and 0.58 ± 0.01, respectively) by TiO 2 NPs (15-50 nm, 0.1 mg/mL in the solution) was observed by Anaya-Esparza et al [19]. Ripolles-Avila et al [20] reported that both anatase (crystal phase, 7 nm) and a combination of anatase-rutile (80:20 wt/wt, 21-nm size) in the range from 0.78 to 100 μg TiO 2 /mL of nutrient broth significantly reduced the growth of S. enterica var.…”
Section: Discussionmentioning
confidence: 82%
“…Titanium dioxide is one of the most studied inorganic nanoparticles due to their versatility for diverse research areas (materials, physics, gas sensor, energy production, wastewater treatment, cosmetics, and food science) [6,58,59]. The wide use of titanium dioxide is supported by its photocatalytic performance, antimicrobial, electrical, ultravioletblocking, and adsorptive properties, biocompatibility, chemical stability, high surface area, low-cost, and safe production [60,61].…”
Section: Titanium Dioxide (Tio 2 )mentioning
confidence: 99%